UJI AKTIVITAS EKSTRAK BUAH MERAH (Pandanus conoideus) SEBAGAI HEPATOPROTEKTOR PADA HATI MENCIT GALUR SWISS YANG DIINDUKSI DENGAN CCl4 - Arina Swastika Maulita (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2010)
Liver is an the important organ, it plays an essential role in maintaining the biological equilibrium of vertebrates. Reactive oxygen species (ROS) play an important role in pathological changes in the liver. The research has been carried out to know the potential use of buah merah (Pandanus conoideus) extract as hepatoprotrctive agent against CCl4 poisoning in mice. In this study, the hepatoprotective activity was determined by the reduction of SGPT (serum glutamic pyruvate transaminase) and SGOT (serum glutamic oxaloacetic transaminase) level. Application of buah merah extract significantly (p< 0,05) reduced SGPT and SGOT level. Microscopically, several changes were found, such as severe hydrofic degeneration and necrosis at liver cell that treated by CCl4. Base on histological examination of application of buah merah extract, could inhibit damage and reduced the degeneration and necrosis of liver cell. Keywords: buah merah, SGPT, SGOT, hepatoprotective.